2021
DOI: 10.1186/s13741-021-00181-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemic lidocaine on post-operative opioid consumption in ambulatory surgical patients: a meta-analysis of randomized controlled trials

Abstract: Background Ambulatory surgical procedures continue to grow in relevance to perioperative medicine. Clinical studies have examined the use of systemic lidocaine as a component of multimodal analgesia in various surgeries with mixed results. A quantitative review of the opioid-sparing effects of systemic lidocaine in ambulatory surgery has not been investigated. The primary objective of this study was to systematically review the effectiveness of systemic lidocaine on postoperative analgesic outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Similar to other studies, we found that the addition of perioperative lidocaine infusion reduced the morphine requirement in the first 24 hours post-operatively, as well as time to first mobilization, resumption of bowel function and LOS [26][27][28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other studies, we found that the addition of perioperative lidocaine infusion reduced the morphine requirement in the first 24 hours post-operatively, as well as time to first mobilization, resumption of bowel function and LOS [26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…Recent literature J Gastrointestin Liver Dis, June 2023 Vol. 32 No 2: 156-161 linked intravenous lidocaine administration with more than just less opioid consumption, but even lower pain scores, less post-operative nausea and vomiting, reduced duration of ileus and a shorter hospital stay [28,33,34]. Our results confirmed the results of a number of studies focusing on early recovery after abdominal surgeries when patients received intravenous lidocaine [34][35][36][37].…”
Section: Discussionsupporting
confidence: 82%
“…For comparing our results with prior literature, it can be noted that the use of IV lidocaine has been most commonly reported in a surgical setting ( 42 ). While the majority of studies on surgical patients indicate that lidocaine is an effective analgesic for postoperative pain control ( 10 , 11 ), few trials have indicated that systemic lidocaine may offer no beneficial effect in the postoperative period ( 43 , 44 ). However, it is important to note that majority of the studies assessing the efficacy of IV lidocaine in a surgical setting have compared the drug with placebo or used IV lidocaine as an adjunct to a baseline analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…While lidocaine is commonly used for nerve blocks and infiltration anesthesia, the drug also acts an analgesic when administered intravenously (IV) ( 9 ). Several RCTs have shown that the use of IV lidocaine significantly reduces postoperative opioid consumption, decreases pain intensity, and shortens hospital stay in surgical patients ( 10 , 11 ). A meta-analysis of 26 studies by Zhu et al ( 12 ) have demonstrated that IV lidocaine is effective for the management of patients with neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…As long as the maximum doses (taking into consideration wound infiltration and eventual nerve blocks) are respected, this is a noncontroversial drug with few adverse effects, being useful for analgesia especially in gynaecological and intra-abdominal procedures [53 ▪ ,54]. It may be used with a loading dose of 1 mg/kg, then running with 2 mg/kg/h during surgery, and 1 mg/kg/h during stay in the recovery unit.…”
Section: Other Measures and Drugsmentioning
confidence: 99%